Brief note: First report of the genus Tetramereia Klages, 1907 (Coleoptera: Scarabaeidae: Phanaeini) in Colombia - Notes to its distribution - Noriega-A., Jorge Arí; Rengifo, Juan Manuel; Vaz-de-Mello, Fernando Z. (Biota Colombiana, 2008)
-